Different factors influencing students’ in-class oral active participation, considering english domain in students of Intermediate English I, at Foreign Languages Department - Rivera Marroquin, Francisco
Throughout the history of education there have been several attempts to innovate and improve the methodologies to improve the teaching and learning process. Those changes have had a minimal, but important advance because the positivist- knowledge centred view that had been pervading education during many years has now been superseded by a person centred paradigm which establishes that the most important part of any educational process is the student . Even so, there must be an important consideration to prepare students in order to be able to deal with the demand of qualification needed to perform a task and obtain a job. It is therefore a big task for teachers not only to prepare students for having an acceptable performance in their jobs, but also to form competitive persons whose personality can lead them to higher levels of competence and adaptation. The role of a teacher is not just to make the students focus on developing their knowledge of the world. Teachers need to help students develop their skills in order to master them in different contexts in the target language. In other words, the way students perform in class in terms of oral active participation might be fundamental to create a participation culture which may enable them to perform in other areas of their personal and professional life.